2019
DOI: 10.1021/acs.jpcc.9b08492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Spatial Conformation of Charged Ligands on the Optical Properties of Gold Nanoclusters

Abstract: Photoluminescent gold nanoclusters (Au NCs) were synthesized in one step in aqueous conditions using a mixture of glutathione and (mono or multivalent) glutathione modified arginine peptides. By controlling the ratio of co-ligands, we investigated how the multivalency and the amount of arginines influenced the growth of Au NCs, their surface chemistry, their colloidal stability, and their optical properties. We demonstrated using two-dimensional nuclear magnetic resonance spectroscopy that the organisation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…In this case, the uorescence enhancement has been mainly attributed to a rigidication of the ligand shell around the gold core reducing the non-radiative losses. 25 HRTEM pictures (Fig. 1B) showed metal core size below 3 nm for all samples except for AuSG-3Arg which contained larger particles (>10 nm, NPs).…”
Section: Au Ncs Characterizationmentioning
confidence: 96%
See 3 more Smart Citations
“…In this case, the uorescence enhancement has been mainly attributed to a rigidication of the ligand shell around the gold core reducing the non-radiative losses. 25 HRTEM pictures (Fig. 1B) showed metal core size below 3 nm for all samples except for AuSG-3Arg which contained larger particles (>10 nm, NPs).…”
Section: Au Ncs Characterizationmentioning
confidence: 96%
“…Au NCs stabilized by SG or SG-XArg (X ¼ 1, 2 or 3) were prepared by wet chemistry as described in our previous study 25 and reported in the ESI † (Section 1). Au NCs were dissolved in PBS (10 mM, pH 7.4) at 4 mgAu mL À1 and ltered through a 0.2 mm syringe lter (PTFE membrane).…”
Section: Synthesis Of Au Ncsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, PAGE is also often used to examine the distribution of chemical compositions of a product, optimize reaction conditions, elucidate the degraded processes, and track reactions. [102][103][104][105][106][107][108][109][110] For example, Tsukuda and Teranishi et al observed that Au 25 (SG) 18 was a major product when a triphenylphosphine (PPh 3 )-protected Au cluster was mixed with glutathione (GSH). They attempted to optimize the reaction conditions to selectively synthesize such a stable cluster with atomic precision.…”
Section: Page Separation For Reaction Controlmentioning
confidence: 99%